Anonim şirketlerde temsil ve temsil yetkisinin devri - Kuru, Özge (My University, 2022)
Anonim şirketler tüzel kişiliği haiz olup, iradelerini organları aracılığıyla açıklarlar (TMK m. 50/ 1). Anonim şirketlerde kural olarak temsil yetkisi yönetim kurulu tarafından kullanılır. Yönetim kurulu temsil yetkisini esas sözleşmede aksi öngörülmemiş veya yönetim kurulu tek kişiden oluşmuyorsa, çift imza ile kullanır. Bununla birlikte istisnai durumlarda, temsil yetkisinin kayyım veya tasfiye memurları tarafından da kullanılması mümkündür. 6762 sayılı Türk Ticaret Kanunu’ndan farklı olarak 6102 sayılı Türk Ticaret Kanunu’nda ultra vires ilkesi kaldırılmıştır. Yönetim kurulunun temsil yetkisinin kapsam ve sınırları TTK m. 371’de belirlenmiştir. Bu kapsamda her ne kadar yönetim kurulunun şirket amaç ve işletme konusu çerçevesinde hareket etmesi gerekmekteyse de, temsile yetkili olanların şirket işletme konusu dışında yaptığı işlemler de şirketi bağlar. Şirket ancak üçüncü kişinin işlemin işletme konusu dışında kaldığını bildiği ya da durumun gereğinden bilebilecek durumda olduğunun ispatı halinde işlemin geçersizliğini ileri sürebilir. Yönetim kurulu temsil yetkisini içlerinden bir veya daha fazla yönetim kurulu üyesine ya da üçüncü kişilere devredebilir. Bu durumda en az bir yönetim kurulu üyesinin temsile yetkili olması şarttır. Anonim şirketlerin temsilinde ticari temsilci veya ticari vekil gibi bağımsız tacir yardımcılarından da faydalanılabilir (TTK m. 368). Bu kişiler yönetim kurulu tarafından atanırlar. Ayrıca yönetim kurulunun temsil yetkisini TTK m. 370/ 2’ye uygun olarak devredebilmesi de mümkündür.

Joint-stock companies have legal personality and express their will through their organs. As a rule, representation authority in joint-stock companies is used by the board of directors. The authority to represent the board of directors is exercised with two signatures if the opposite is not stipulated in the articles of association or the board of directors is not composed of a single person. However, in exceptional cases, it is possible to use the power of representation by trustees or liquidators. Unlike the Turkish Commercial Code numbered 6762, the ultra vires principle was abolished in the Turkish Commercial Code numbered 6102. The scope and limits of the representation authority of the board of directors are determined in TCC article 371. In this context, although the board of directors must act within the framework of the company's purpose and scope of activity, the transactions realised by the persons authorized to represent the company outside the scope of the company's activity are binding for the company as well. The company can claim the invalidity of the transaction only if it is proven that the third party knows that the transaction is outside the scope of the activity or is in a position to have known about the situation. The registered attorney (ticari temsilci) and commercial agency (ticari vekil) can also be utilized in the representation of joint-stock companies (TCC art. 368). These persons are appointed by the board of directors. It is also possible for the board of directors to transfer its representation authority in accordance with TCC article 370/ 2. The board of directors may delegate its representation authority to one or more members of the board of directors or to third parties. In this case, at least one member of the board of directors must be authorized to represent.
Keywords: Anonim şirketler; Anonim şirketlerin temsili; commercial agency; Corporation law; kayyımın temsil yetkisi; limits of representation; power of attorney of liquidators; Representation of joint-stock companies; scope of representation; Stock companies; Şirket hukuku; tasfiye memurlarının temsil yetkisi; temsil yetkisinin devri; temsil yetkisinin kapsamı; temsil yetkisinin sınırları; the registered attorney; ticari temsilci; ticari vekil; transfer of authority to represent; trustee’s power of attorney; Turkey; Türkiye